Physiological examination of some industrial wastes under laboratory conditions - Tóth, Brigitta (Acta Agraria Debreceniensis, 2012)
I would like to draw the attention to the different side-products and wastes that contain lots of organic matter, micro and macro elements, and the fact that they do not have any harmful effect. These materials can be used as micronutrient fertilizers, therefore quantity of the produced CO2 and other greenhouse gases will decrease. Compost, sewage sludge and lime sludge were used in our experiments. The usability of these materials in crop production was examined in crop production within laboratory conditions.